1963
DOI: 10.1029/jz068i016p04731
|View full text |Cite
|
Sign up to set email alerts
|

The relation of solar radiation to evapotranspiration from cotton

Abstract: Evapotranspiration affects the irrigation requirements of crops, and a simple method is needed for determining ET. The evapotranspiration equivalent of solar radiation (RS) is easily computed from data readily available from the U.S. Weather Bureau. The ET/RS ratio for cotton irrigated at Watkinsville, Georgia, showed that Rs data can be used to predict irrigation needs when the ET/RS ratio, daily rainfall, and available water capacity of the soil are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This effect is certainly larger in the tropical rain forest of Tahiti [55]. Land evapotranspiration (soil evaporation plus plant transpiration) is driven, for a large part, by insolation ( [56,57] and Figure 16), the vegetation cover [58], and the surface wind and surface temperature [59,60]. Research about evapotranspiration is a very active field nowadays.…”
Section: Influence Of the Topography On Zwd And Pw Estimatesmentioning
confidence: 99%
“…This effect is certainly larger in the tropical rain forest of Tahiti [55]. Land evapotranspiration (soil evaporation plus plant transpiration) is driven, for a large part, by insolation ( [56,57] and Figure 16), the vegetation cover [58], and the surface wind and surface temperature [59,60]. Research about evapotranspiration is a very active field nowadays.…”
Section: Influence Of the Topography On Zwd And Pw Estimatesmentioning
confidence: 99%
“…Carreker (2) has recently shown that the solar radiation method for estimating ET can be used to predict irrigation needs when ET/Rs, daily rainfall, and available water capacity of the soil are known.…”
mentioning
confidence: 99%